Mitigasi Perubahan Iklim dan Dampak Pengelolaan Sumber Daya Agraria: Wawasan dari Indonesia - Junarto, Rohmat (Tunas Agraria, 2023)
Indonesia is the fourth-highest contributor to carbon emissions in the world, which influence global climate change. Extra efforts are needed to restore the nation's image internationally by prioritizing real efforts. This effort can be carried out by embracing all stakeholders in multiple sectors. The aim of this study is to determine the extent of the realization of the efforts of the Indonesian government and stakeholders involved in mitigating and adapting to the impacts of climate change on the forest and land sectors at the local, regional, and international levels. This research uses a qualitative method with a literature study approach. The data analysis used is a narrative-descriptive analysis. This research reveals that in the forest and land sectors, the Indonesian government has succeeded in controlling and managing peatlands, rehabilitating mangrove and seagrass areas, providing access to forest management through social forestry schemes, structuring forest areas, and optimizing the role of state-owned enterprises. Apart from that, in order to achieve net zero emissions (NZE), Indonesia is able to replace the use of fossil energy with renewable energy. The government has carried out this effort by issuing a number of green financing policies and incentives.   Indonesia menjadi penyumbang emisi karbon tertinggi keempat di dunia yang mempengaruhi perubahan iklim global. Perlu usaha ekstra untuk mengembalikan citra bangsa dimata internasional dengan mengedepankan usaha nyata. Usaha tersebut dapat dilakukan dengan merangkul segenap multi stakeholder pada multi sektor. Tujuan kajian ini adalah untuk mengetahui sejauh mana realisasi dari upaya pemerintah Indonesia dan stakeholder yang terlibat dalam memitigasi dan mengadaptasi dampak perubahan iklim pada sektor hutan dan lahan di level lokal, regional dan internasional. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi literatur. Analisis data yang digunakan adalah analisis deskriptif naratif. Penelitian ini mengungkap bahwa pada sektor hutan dan lahan Pemerintah Indonesia berhasil mengendalikan dan mengelola lahan gambut; merehabilitasi kawasan mangrove dan lamun; memberikan akses pengelolaan hutan melalui skema perhutanan sosial; melakukan penataan kawasan hutan; dan mengoptimalkan peran Badan Usaha Milik Negara. Selain itu, dalam rangka mencapai Net Zero Emission (NZE), Indonesia mampu mengurangi penggunaan energi fosil dengan energi terbarukan. Usaha tersebut dilakukan pemerintah dengan mengeluarkan sejumlah kebijakan dan insentif pembiayaan hijau.